(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
Through discourses constructed in historical, cultural and social contexts, women face difficulties regarding the insertion, permanence and ascension in the scientific-technological career. In this context, we aim to understand and analyze what is shown in research on gender issues and Science-Technology (ST) in science education in Brazil. To do so, we present a qualitative research, a state of the art, which had as corpus of analysis theses and dissertations present in the repository of the Brazilian Institute of Information in Science and Technology. Methodologically, we used the Textual Discourse Analysis, from which three categories emerged, namely: (1) The discourse of women’s non-belonging in ST (2) The (in)visibility of female models who did/do ST and (3) Scientist-mothers and the multiplied workdays. We realize that the feminine gender faces stereotypes and prejudices that end up influencing its inclusion and path in ST. In the search for making ST visible and showing it as a possible career for the female gender, family, school, teachers, and the promotion of public policies of support and incentive are some of the essential means for this.